A Woman's self - esteem : - Branden, Nathaniel (Jossey-Bass Publishers, 1998)
In a time when women are faced with many outside demands--career, family, community--this book will give them the tools and inspiration needed to remain grounded. A must read!"--Barbara McFarland, psychologist and author of My Mother Was Right Based on the intimate stories of women who have struggled with issues of self-esteem, this invaluable book offers step-by-step guidance for women who want to transform themselves and create lives that are powerful, energized, and motivated. A Woman's Self-Esteem is also a guide for helping women learn the impact they can make on their own lives and how their positive actions will result in a stronger sense of competence and self-worth. A pioneer in the field of self-esteem, psychotherapist Nathaniel Branden explains that the foundation of a healthy self-esteem rests on six key practices or virtues--living consciously, self-acceptance, self-responsibility, self-assertiveness, purposeful living, and personal integrity--and reveals how women can cultivate these essential virtues to reach their full potential. The author?s inspiring, real-life vignettes show how women have come to terms with these complex issues by breaking away from self-sabotaging patterns and taking the necessary steps to create more satisfying lives. In A Woman's Self-Esteem, Branden debunks common myths and reminds us that self-esteem is not a gift given to us by others. Branden offers a revealing examination of the special issues that women grapple with including romantic love, jealousy, fear of selfishness, expressing anger, defensiveness, and success anxiety. Filled with creative exercises, A Woman's Self Esteem was developed to enhance personal development and fortify self-esteem.